Red, White, & True Blue Mallory : Mallory McDonald Series #11 - Friedman, Laurie B., 1964-; Kalis, Jennifer (Minneapolis, MN : Carolrhoda Books, 2009)
Mallory's journal of her fourth-grade trip to Washington D.C. reveals how much fun she has, despite a loose tooth, being upset with her best friend Mary Ann and getting separated from her class in a museum.
Keywords: School field trips -- Juvenile fiction; Tourism -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Diaries -- Juvenile fiction; School field trips -- Fiction; Tourism -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Diaries -- Fiction; Washington (D.C.) -- Juvenile fiction; Washington (D.C.) -- Fiction; High interest-low vocabulary books